Probabilistic seismic hazard assessment of Muğla, Turkey - İnce, Gökçe Çiçek; Yılmazoğlu, Mehmet Uğur (Springer Science and Business Media LLC, 2021)
Mugla Province, which has been selected as the study area, is located in the Aegean Extension Region (AER), where seismic motions are widely observed. Moreover, the AER is the most active part of the Eastern Mediterranean Region in terms of seismic activity, and this seismicity has been continuing increasingly. This study aims to determine the seismic hazard of Mugla Province and its surroundings by using the probabilistic seismic hazard method. The earthquake dataset including 19,824 seismic records that were used in the research was obtained from the national and international earthquake catalogs. The data about the active fault zones in the study area were acquired from the General Directorate of Mineral Research and Exploration. The seismic source zones were generated as homogeneous areas as possible taking into account the active fault zones. The earthquakes in seismic source zones were eliminated based on the time and distance frames. The annual recurrence relationships of the source zones were determined using the least-squares method taking into account the earthquakes with a magnitude of 5 or above. The peak acceleration values on the bedrock were calculated using the attenuation relationships of the selected local and global ground motion prediction models. The calculations were performed using the SEISRISK III software package utilizing the homogeneous Poisson Process Model according to the exceedance probability of 10% for 50 years (corresponding to the return period of 475 years). The peak acceleration values on bedrock were found to range between 0.11 and 0.42. The study revealed that the Gokova fault zone (Zone 4) was the most active source in terms of the seismic hazard in the region and that the seismic hazard of the southwestern part of the region was greater compared to other parts.
Keywords: 13. Climate action